Phenotypic, functional, and metabolic heterogeneity of immune cells infiltrating non–small cell lung cancer - Aramini, Beatrice; Masciale, Valentina; Samarelli, Anna Valeria; Dubini, Alessandra; Gaudio, Michele; Stella, Franco; Morandi, Uliano; Dominici, Massimo; De Biasi, Sara; Gibellini, Lara; Cossarizza, Andrea (Frontiers in Immunology, 2022)
Lung cancer is the leading cancer in the world, accounting for 1.2 million of new cases annually, being responsible for 17.8% of all cancer deaths. In particular, non–small cell lung cancer (NSCLC) is involved in approximately 85% of all lung cancers with a high lethality probably due to the asymptomatic evolution, leading patients to be diagnosed when the tumor has already spread to other organs. Despite the introduction of new therapies, which have improved the long-term survival of these patients, this disease is still not well cured and under controlled. Over the past two decades, single-cell technologies allowed to deeply profile both the phenotypic and metabolic aspects of the immune cells infiltrating the TME, thus fostering the identification of predictive biomarkers of prognosis and supporting the development of new therapeutic strategies. In this review, we discuss phenotypic and functional characteristics of the main subsets of tumor-infiltrating lymphocytes (TILs) and tumor-infiltrating myeloid cells (TIMs) that contribute to promote or suppress NSCLC development and progression. We also address two emerging aspects of TILs and TIMs biology, i.e. their metabolism, which affects their effector functions, proliferation and differentiation, and their capacity to interact with cancer stem cells.